2016
DOI: 10.1539/joh.16-0136-br
|View full text |Cite
|
Sign up to set email alerts
|

Generation rate and particle size distribution of wood dust by handheld sanding operation

Abstract: Objectives: The International Agency for Research on Cancer (IARC) and Japan Society for Occupational Health (JSOH) classified wood dust as a human carcinogen. Former studies have suggested that sanding with a portable sander is one of the processes that are liable to cause highest exposure to wood dust. However, the wood dust by sanding operation has not been investigated sufficiently. In this study, the generation rate and the particle size distribution of the wood dust produced by handheld sanding operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Comparing results of wood dust concentration evaluation from different experimental setups and field measurements reported in the literature is very difficult. However, results of this study are in agreement with previous studies [4,5,7,8,9,10,12,16] who found that harder woods and coarsest abrasive grit produced a lower rate of dust production. Various limitations to this study need to be considered.…”
Section: Discussionsupporting
confidence: 93%
“…Comparing results of wood dust concentration evaluation from different experimental setups and field measurements reported in the literature is very difficult. However, results of this study are in agreement with previous studies [4,5,7,8,9,10,12,16] who found that harder woods and coarsest abrasive grit produced a lower rate of dust production. Various limitations to this study need to be considered.…”
Section: Discussionsupporting
confidence: 93%
“…During wood processing, dust is created as a by-product [1][2][3][4][5][6][7], and plays a negative role in assessing the risk of fire [8] or explosion [9][10][11][12][13][14]. Wood fust also poses a significant risk to the health of the human body [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…When the specimens were sanded with a fine sand paper, the mass median aerodynamic diameters of beech wood dust and cypress wood dust were 9.0 μm and 9.8 μm, respectively. Respirable wood dust is able to be controlled by general ventilation with an air flow rate of over 0.7 to 4.2 m 3 /min (Ojima 2016). The mass concentration of the smallest dust particles has a negative linear relation to the total air flow rate of the exhaust system during sawing with a circular saw (Palubicki et al 2020).…”
Section: Introductionmentioning
confidence: 99%